2020
DOI: 10.1038/s41598-020-73749-y
|View full text |Cite
|
Sign up to set email alerts
|

Sectoral activation of glia in an inducible mouse model of autosomal dominant retinitis pigmentosa

Abstract: Retinitis pigmentosa (RP) is a group of blinding disorders caused by diverse mutations, including in rhodopsin (RHO). Effective therapies have yet to be discovered. The I307N Rho mouse is a light-inducible model of autosomal dominant RP. Our purpose was to describe the glial response in this mouse model to educate future experimentation. I307N Rho mice were exposed to 20,000 lx of light for thirty minutes to induce retinal degeneration. Immunofluorescence staining of cross-sections and flat-mounts was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…We then quantified the number of microglia/macrophages by immunostaining the microglia/macrophage marker CD68 in flat-mounts of retinal explants (Figure 9, G-M, and Supplemental Figure 12). Under DMSO treatment, Rho P23H/+ retinal explants showed over 2 times as many CD68 + cells compared with WT retinal explants, confirming that the rod cell stress and death indeed activate retinal microglia as seen in vivo (Figure 9, G, J, and M) (44,45). YC-001 decreased CD68 + cell number in both Rho P23H/+ and WT retinal explants by > 5 fold compared with DMSO controls (Figure 9, H, K, and M), suggesting a potent inhibition of microglia/macrophages by YC-001.…”
Section: Resultsmentioning
confidence: 54%
“…We then quantified the number of microglia/macrophages by immunostaining the microglia/macrophage marker CD68 in flat-mounts of retinal explants (Figure 9, G-M, and Supplemental Figure 12). Under DMSO treatment, Rho P23H/+ retinal explants showed over 2 times as many CD68 + cells compared with WT retinal explants, confirming that the rod cell stress and death indeed activate retinal microglia as seen in vivo (Figure 9, G, J, and M) (44,45). YC-001 decreased CD68 + cell number in both Rho P23H/+ and WT retinal explants by > 5 fold compared with DMSO controls (Figure 9, H, K, and M), suggesting a potent inhibition of microglia/macrophages by YC-001.…”
Section: Resultsmentioning
confidence: 54%
“…TrueBlack is a commercial AF quenching reagent that reduces tissue sections AF from lipofuscin and less efficiently from other sources like red blood cells and extracellular components. TrueBlack has been used for AF reduction in a wide range of human and mouse tissue types, such as the brain [ 36 , 37 , 38 , 39 ], retina [ 40 , 41 ], heart [ 42 , 43 ], lung [ 44 , 45 ], and liver tissue [ 46 , 47 ]. SBB is a superlipophilic diazo dye used for staining a wide variety of lipids [ 48 , 49 ] and some proteins [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…TrueBlack is provided as a 20X solution that can be diluted in ethanol according to the required dilution, usually 1X, according to the manufacturer’s instructions. However, TrueBlack has been used in different concentrations [ 10 , 79 , 80 ] and incubation times [ 41 , 81 , 82 ] for AF reduction. The ability to optimize TrueBlack treatment is helpful when treating tissues rich with autofluorescent material, such as the adrenal glands, to avoid IF signal masking by intensive dark tissue staining.…”
Section: Discussionmentioning
confidence: 99%
“…In the P23H rat, it was found that microglial infiltration into the subretinal space correlated with the progression of the degeneration, and that activation of systemic inflammation accelerated the loss of photoreceptors [ 47 , 61 ]. Microglial activation in P23H [ 47 ] and other rodent models of retinitis pigmentosa caused by rhodopsin mutations [ 62 , 63 , 64 ] has been described as contributing to the death of the photoreceptors, and interventions that reduce cell death correlate with reduced microglial activation [ 65 ] Our data confirm the converse of this postulate, which is that increased cell death as a result of either ⍺A- and ⍺B-crystallin knockout is associated with an increased inflammatory response and increased microglial activation. Future work in our knockout mice will seek to assess whether anti-inflammatory interventions can ameliorate cell death, even in the absence of the ⍺A- and ⍺B-crystallins.…”
Section: Discussionmentioning
confidence: 99%